Emotional affordances in virtual reality-based learning environments. Germany: Lambert Academic Publishing - Chuah, Kee Man; Chen, Chwen Jen; Teh, Chee Siong (LAP LAMBERT Academic Publishing, 2011)
This book offers a fresh perspective by proposing a framework for emotional considerations in instructional design particularly in the case of virtual reality (VR)-based learning environments. The theoretical foundation and practical considerations of the framework are discussed thoroughly. A VR-based learning environment related to the teaching of pedestrian safety skills to young learners is used as a case for the application of the proposed framework. The results of the experiment indicate the potential and feasibility of the approach in uncovering salient design elements of VR-based learning environments that can induce positive emotions among the learners. Instructional designers and researchers who want to investigate further on the emotional dimension when designing instructional materials would find this book useful.